PEMBERDAYAAN KADER DAN KELUARGA DALAM PENINGKATAN KOMUNIKASI EFEKTIF PADA LANSIA - Dewi Utari; Ferianto Ferianto; Suwarno Suwarno; Wenny Savitri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
Aged people will experience several changes in all aspects of life including, physical, psychological, spiritual, and social. Their altered condition such as hearing deprivation, loss of vision, or fluctuating emotions will affect how the way they communicate with other family members. Thus, the family should be more concerned regarding this issue, unless they will have ineffective communication. Moreover, it may lead to trigger a conflict among family members. To unravel this problem, an education on effective communication for aged people using a module will help them to improve strategies for managing the elderly's communication problems. This activity involved 67 families with elderly and 7 health volunteers in Kelurahan Patangpuluhan Wirobrajan Yogyakarta. The result showed that education could elevate the score of effective communication among aged people, both family, and health volunteers. However, health volunteers had a higher average score than family